The Aβ40 and Aβ42 peptides self-assemble into separate homomolecular fibrils in binary mixtures but cross-react during primary nucleation1. Issue 7 (15th July 2015) - Cukalevski, Risto; Yang, Xiaoting; Meisl, Georg; Weininger, Ulrich; Bernfur, Katja; Frohm, Birgitta; Knowles, Tuomas P. J.; Linse, Sara
<x xml:space="preserve">Abstract</x> Reaction network starting from monomer mixtures of Aβ40 and Aβ42. Interaction at the level of primary nucleation only accelerates Aβ40 fibril formation. Separate fibrils form as secondary nucleation and elongation are highly specific.